Implementasi Pembelajaran Individual dalam Meningkatkan Pemahaman Siswa SMP dan SMK Sabilurrasyad - Prihatiningsih, Retno; Falah, M Fajrul; Khoiri, Ahmad; Ilham Zakia, Muhammad; Anugraheni, Fikri Amalia (LPPM Sekolah Tinggi Islam Kendal, 2025)
Education is one of the main pillars in developing high-quality human resources. One of the major challenges in education today is how to create a learning process that accommodates individual differences among students. This is particularly relevant for schools with diverse student characteristics, such as SMP and SMK Sabilurrasyad, which consist of students with different social backgrounds, academic abilities, interests, and learning styles. Conventional learning, which is still dominated by lecture methods, tends to provide limited opportunities for students to learn at their own pace and in their preferred learning style. Therefore, a more flexible, student-centered approach is needed, one of which is individualized learning. This study aims to explore the implementation of individualized learning as an effort to improve students’ understanding, as well as to identify the factors that support and hinder the application of this strategy. The focus of the research is directed toward how teachers design, implement, and evaluate individualized learning to help students achieve more optimal learning outcomes. The research uses a descriptive qualitative approach, as it is appropriate for describing educational phenomena in depth and within context. Data were collected through several techniques, including direct observation of the learning process, interviews with teachers and students, and documentation of learning materials, students’ work results, and teachers’ evaluation records. Data analysis was carried out interactively through stages of data reduction, data presentation, and conclusion drawing, so that the findings accurately represent the actual conditions in the field. The implementation of individualized learning has been proven to have a positive impact on students’ understanding. Most students reported feeling more comfortable exploring the material and reviewing sections they did not yet understand without feeling left behind by their peers. Results from formative and summative evaluations showed an increase in the class average scores after the implementation of individualized learning, both at SMP and SMK levels. This change indicates that this strategy can significantly improve students’ conceptual understanding and skills. Based on these findings, it can be concluded that individualized learning is an effective approach to improving students’ understanding at SMP and SMK Sabilurrasyad. This strategy provides students with the opportunity to learn according to their capacity and learning style, fosters independence, and enhances learning outcomes. However, for individualized learning to be implemented sustainably, careful planning, adequate facilities, and intensive mentoring for both teachers and students are required. This study is expected to serve as a reference for other schools that wish to implement individualized learning as an alternative teaching strategy that adapts to the diversity of learners.